Work Attitude, Ethics and Performance: Exploring Organizational Influences on Health Workers Performance in Selected Healthcare Institution in Nigeria - Bakare, Lawal; Onabanjo, Leke K.; O. Falowo, Oluwafisayo; O. Owoladed, Oladepo (Management Research Journal, 2025)
Issues regarding work ethics and staff attitudes in Nigeria's healthcare sector have a profound impact on service delivery. This study examines the complex relationship between work attitudes and the performance of health workers at University College Hospital, Ibadan, emphasising the organisational, cultural, and individual elements that impede ethical conduct. A quantitative methodology was employed to gather data through structured questionnaires distributed to 200 intentionally selected healthcare workers. Analysis was performed with descriptive and inferential statistics, Structural Equation Modelling, and Confirmatory Factor Analysis through SPSS v22. The findings indicate a robust direct correlation between work ethics and employee behaviour (β = 0.769, p < 0.05), implying that even slight enhancements in ethical conduct can markedly improve workplace behaviour. The impact of work ethics is partially mediated by dedication, attitude, and integrity (β = 0.110, p < 0.05), suggesting that intrinsic qualities influence ethical outcomes. Organisational, cultural, and individual barriers were identified as major contributors to unethical behaviour (p = 0.012), with each further increase in these limitations correlating with heightened negative conduct (β = 0.669). The study highlights the pressing necessity for systemic reforms to foster a culture of professionalism and ethical excellence, providing significant insights for policymakers, administrators, and scholars in healthcare management and organisational behaviour.